The risk of empathy: longitudinal associations between empathy and burnout. Issue 12 (29th November 2021) - Altmann, Tobias; Roth, Marcus
Abstract: Objective: Prior research on the relation between empathy and burnout in social professions appears to be inconsistent. Whereas some studies have claimed that empathy functions as a buffer against burnout, others have argued that empathy contributes to the development of burnout. One explanation for this disparity may be methodological as most studies have relied on cross-sectional single-measure designs. To examine their cross-sectional and longitudinal associations, the present study analyzed cross-lagged data of several measures of empathy and burnout. Design: Data from two longitudinal studies with three to twelve months between measurements were analyzed. The samples contained 172 nursing students and 186 nurses, respectively. Main Outcome Measures: Empathy was assessed using the Interpersonal Reactivity Index, the Toronto Empathy Questionnaire, the Geneva Emotion Recognition Test, and the Social Mindfulness Test Paradigm. Burnout was assessed using the Maslach Burnout Inventory, the Irritation Scale, and the Copenhagen Burnout Inventory. Results: Results showed significant cross-sectional correlations between the questionnaire measures of empathy and burnout. However, there was insufficient support for the cross-lagged associations. Conclusions: Associations between empathy and burnout may be attributed to the methodological limitations of cross-sectional designs. However, the influence of potential moderators is discussed as a promising direction of future research.